2021
DOI: 10.1177/2382120520988590
|View full text |Cite
|
Sign up to set email alerts
|

Internal Medicine Residents’ Views About Care Transitions: Results of an Educational Intervention

Abstract: Problem: Suboptimal care transitions can lead to re-hospitalizations. Intervention: We developed a 2-week “Transitions of Care Curriculum” to train first-year internal medicine residents to improve their knowledge and skills to deliver optimal transitional care. Our objective was to use reflective writing essays to evaluate the impact of the curriculum on the residents. Methods: The rotation included: Transition of Care Teaching modules, Transition Audit, Transitional Care Site Visits, and Transition of Care C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…From a personal perspective, RW increases self-awareness [ 114 , 127 , 137 , 161 , 166 , 179 , 185 , 202 , 216 ], self-advancement [ 9 , 131 , 134 , 150 , 168 , 174 , 195 , 205 , 217 , 229 ], facilitates understanding of individual strengths, weaknesses and learning needs [ 112 , 119 , 150 , 152 , 170 , 218 , 219 ], promotes a culture of self-monitoring, self-improvement [ 130 , 172 , 173 , 185 , 193 , 198 , 201 , 210 , 211 ], developing critical perspectives of self [ 193 , 223 ] and nurtures resilience and better coping [ 154 , 160 , 206 ]. RW also guides shifts in thinking and perspectives [ 148 , 149 , 156 , 203 , 207 , 208 ] and focuses on a more holistic appreciation of decision-making [ 37 , 118 , 126 , 174 , 177 , 194 , 196 , 199 , 200 , 224 – 226 ] and their ramifications [ 37 , 112 , 116 , 130 , 13...…”
Section: Resultsmentioning
confidence: 99%
“…From a personal perspective, RW increases self-awareness [ 114 , 127 , 137 , 161 , 166 , 179 , 185 , 202 , 216 ], self-advancement [ 9 , 131 , 134 , 150 , 168 , 174 , 195 , 205 , 217 , 229 ], facilitates understanding of individual strengths, weaknesses and learning needs [ 112 , 119 , 150 , 152 , 170 , 218 , 219 ], promotes a culture of self-monitoring, self-improvement [ 130 , 172 , 173 , 185 , 193 , 198 , 201 , 210 , 211 ], developing critical perspectives of self [ 193 , 223 ] and nurtures resilience and better coping [ 154 , 160 , 206 ]. RW also guides shifts in thinking and perspectives [ 148 , 149 , 156 , 203 , 207 , 208 ] and focuses on a more holistic appreciation of decision-making [ 37 , 118 , 126 , 174 , 177 , 194 , 196 , 199 , 200 , 224 – 226 ] and their ramifications [ 37 , 112 , 116 , 130 , 13...…”
Section: Resultsmentioning
confidence: 99%
“…6 In 2021, Johns Hopkins University School of Medicine implemented a program after polling residents and discovering their awareness of gaps in the transition of care. 7 In 2002, pharmacists evaluated the impact of follow-up telephone calls to recently hospitalized patients. This group of pharmacists found that these calls were associated with increased patient satisfaction, resolution of medication-related problems and fewer emergency department returns.…”
Section: Discussionmentioning
confidence: 99%